Older Adults Mount Less Durable Humoral Responses to Two Doses of COVID-19 mRNA Vaccine but Strong Initial Responses to a Third Dose . (11th May 2022) - Mwimanzi, Francis; Lapointe, Hope R; Cheung, Peter K; Sang, Yurou; Yaseen, Fatima; Umviligihozo, Gisele; Kalikawe, Rebecca; Datwani, Sneha; Omondi, F Harrison; Burns, Laura; Young, Landon; Leung, Victor; et al.
Abstract: Background: Third coronavirus disease 2019 (COVID-19) vaccine doses are broadly recommended, but immunogenicity data remain limited, particularly in older adults. Methods: We measured circulating antibodies against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein receptor-binding domain, ACE2 displacement, and virus neutralization against ancestral and omicron (BA.1) strains from prevaccine up to 1 month following the third dose, in 151 adults aged 24–98 years who received COVID-19 mRNA vaccines. Results: Following 2 vaccine doses, humoral immunity was weaker, less functional, and less durable in older adults, where a higher number of chronic health conditions was a key correlate of weaker responses and poorer durability. One month after the third dose, antibody concentrations and function exceeded post–second-dose levels, and responses in older adults were comparable in magnitude to those in younger adults at this time. Humoral responses against omicron were universally weaker than against the ancestral strain after both the second and third doses. Nevertheless, after 3 doses, anti-omicron responses in older adults reached equivalence to those in younger adults. One month after 3 vaccine doses, the number of chronic health conditions, but not age, was the strongest consistent correlate of weaker humoral responses. Conclusions: Results underscore the immune benefits of third COVID-19 vaccine doses, particularly in older adults. Abstract : One month after a third COVID-19 vaccine dose, older adults mounted comparable humoral responses to both ancestral and omicron SARS-CoV-2 variants compared to younger adults. Results underscore the immune benefits of third COVID-19 vaccine doses, particularly in older adults.